2013
DOI: 10.5964/psyct.v6i2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Processes Underpinning PET and fMRI Techniques With an Emphasis on the Temporal and Spatial Resolution of These Methods

Abstract: In this paper the scanning techniques of PET and fMRI are presented and discussed in technical terms. The main focus of this paper is the physiological processes underpinning these techniques and the ways they operate temporally and spatially. Physiological processes captured by these techniques refer generally to the volume of blood in the brain and the concentration of oxygen in the blood. Temporal and spatial resolution in the case of these methods refers to data collection when the brain is scanned. Tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 153 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…Direct evidence for the underlying molecular changes at the level of individual neurons, however, is beyond the reach of current methods for functional brain imaging. Nevertheless, electroencephalography (EEG) [ 35 , 36 ], magnetoencephalography (MEG) [ 37 , 38 ], near-infrared spectroscopy (NIRS) [ 39 , 40 ], positron emission tomography (PET) [ 41 , 42 , 43 ], and magnetic resonance imaging (MRI) [ 44 , 45 , 46 ] can resolve functional brain states with macroscopic resolution (e.g., EEG has a temporal resolution of milliseconds and MRI has a spatial resolution of millimeters) that can detect cumulative changes in brain volume or excitability acquired over several weeks of training or rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Direct evidence for the underlying molecular changes at the level of individual neurons, however, is beyond the reach of current methods for functional brain imaging. Nevertheless, electroencephalography (EEG) [ 35 , 36 ], magnetoencephalography (MEG) [ 37 , 38 ], near-infrared spectroscopy (NIRS) [ 39 , 40 ], positron emission tomography (PET) [ 41 , 42 , 43 ], and magnetic resonance imaging (MRI) [ 44 , 45 , 46 ] can resolve functional brain states with macroscopic resolution (e.g., EEG has a temporal resolution of milliseconds and MRI has a spatial resolution of millimeters) that can detect cumulative changes in brain volume or excitability acquired over several weeks of training or rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) and fMRI are noninvasive brain imaging techniques. PET evaluates brain activity via blood flow volume, whereas fMRI examines the amount of oxygen in the blood [Varvatsoulias, ]. One previous PET study on 2G signal exposure reported that exposure to an active mobile phone produced a decrease in regional cerebral blood flow bilaterally in the auditory cortex, but no regional cerebral blood flow alterations were revealed in the area of the maximum electromagnetic field, which was probably caused by noise from the battery of the active mobile phone [Haarala et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this study, follows a study by Varvatsoulias (2013) which presents and discusses the neuroscientific background on fMRI and its importance in the scanning of neuronal activation. This study will investigate voice-selective regions in the human auditory cortex that mainly react to human vocal sounds.…”
mentioning
confidence: 99%